2018
DOI: 10.1111/ijpo.12279
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Bisphenol A and phthalates metabolites in the third trimester of pregnancy and BMI trajectories

Abstract: These results suggest sex-specific differences in BMI trajectories by levels of metabolite exposure. Additional studies are needed to consider growth through adolescence in assessing the association of pregnancy exposures on child's BMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 32 publications
2
34
2
3
Order By: Relevance
“…HMWPm with BMI z-scores in boys HMWPm with BMI z-scores in girls (53) MiBP, MBzP, MEHP and MECPP with BMI trajectories in males MECPP with BMI trajectories in female (107) factor expression in mice (108). Most epidemiological studies in humans found that exposure to LMWP metabolites, such as MEP, MBP, MiBP, and HMWP metabolites, MEHHP, and MEOHP, were negatively related to birth weight (82,85,(89)(90)(91)(92)(93)(94)(95)(96), birth length (89,91,95), and circumferences of head, chest or abdominal (84,85,91,94,96,98).…”
Section: Prenatal Phthalate Exposure and Fetal Growthmentioning
confidence: 99%
See 2 more Smart Citations
“…HMWPm with BMI z-scores in boys HMWPm with BMI z-scores in girls (53) MiBP, MBzP, MEHP and MECPP with BMI trajectories in males MECPP with BMI trajectories in female (107) factor expression in mice (108). Most epidemiological studies in humans found that exposure to LMWP metabolites, such as MEP, MBP, MiBP, and HMWP metabolites, MEHHP, and MEOHP, were negatively related to birth weight (82,85,(89)(90)(91)(92)(93)(94)(95)(96), birth length (89,91,95), and circumferences of head, chest or abdominal (84,85,91,94,96,98).…”
Section: Prenatal Phthalate Exposure and Fetal Growthmentioning
confidence: 99%
“…On the contrary, other studies reported inverse or null associations between prenatal phthalate exposure and child's growth (53,(102)(103)(104)(105)(106)(107). One prospective study showed that maternal urinary concentrations of non-DEHP metabolites before delivery, but not DEHP metabolites, were related to a decrease in fat mass, waist circumference, and BMI Z scores of boys at 5 and 7 years ages (102).…”
Section: Prenatal Phthalate Exposure and Child's Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…Individual phthalate metabolite concentrations and molar sum derivatives were natural-log transformed to achieve a normal distribution. All analyses were sex-stratified because phthalate metabolites were previously shown to have sex-specific effects on children's adiposity and on DNA methylation (10, 11, 20). Means, standard deviation (SD), and distributions of phthalate metabolites (geometric means), DNA methylation data, anthropometric outcomes, and maternal education were calculated.…”
Section: Methodsmentioning
confidence: 99%
“…Our prior research in the Early Life Exposure in Mexico to Environmental Toxicants (ELEMENT) project identified associations between phthalate exposure and DNA methylation of H19 and HSD11B2 (20) as well as between phthalate exposure and weight status and adiposity at one childhood time point (10, 11). This study aims to extend the evaluation of phthalate exposures and peri-adolescent adiposity to include trimester-specific measures across pregnancy and repeat measures of adiposity in ELEMENT children.…”
Section: Introductionmentioning
confidence: 99%